PENYELENGGARAAN LAYANAN BIMBINGAN DAN KONSELING KOMPREHENSIF PADA MADRASAH IBTIDAIYAH - Rahman, Imas Kania (ATTA`DIB, 2015)
The purpose of the study are; to know the understanding of head of Madrasah Ibtidaiyah Bogor about guidance and comprehensive counseling; to know the service of guidance and comprehensive counseling that is being done; to know service tools of guidance and comprehensive counseling and; to know difficulties of its application. This study is naturalistic-qualitative of descriptive-analytic. The technique of the study is participant observation; in depth interview, dokumentation and triangulation. The results of the study are; the understanding of head of Madrasah Ibtidaiyah about guidance and comprehensive counseling is not as the rule of Educational ministry no 111 year 2014 (permendikbud No. 111 Tahun 2014); The program is not based yet on independence competence standar; The service tools doesn’t meet minimum standard from ABKIN both personels and facilities; The difficulties faced are less support from the government, less human resources, less funding.